2016
DOI: 10.1021/acschemneuro.5b00316
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Plaque-Associated Oxidative Degradation of Uniformly Radiolabeled Arachidonic Acid

Abstract: Oxidative stress is a frequently observed feature of Alzheimer's disease, but its pathological significance is not understood. To explore the relationship between oxidative stress and amyloid plaques, uniformly radiolabeled arachidonate was introduced into transgenic mouse models of Alzheimer's disease via intracerebroventricular injection. Uniform labeling with carbon-14 is used here for the first time, and made possible meaningful quantification of arachidonate oxidative degradation products. The injected ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 90 publications
(193 reference statements)
0
24
0
Order By: Relevance
“…Early onset of the disease, older age, low education level, and several poor health conditions affect the prevalence rate of the disease and the degree of cognitive impairment (de Souza-Talarico et al, 2016). Increased biomarkers of oxidative stress (Furman et al, 2016), inflammation and chronic neuroinflammation are reported to be associated with many neurodegenerative disorders of central nervous system (CNS) including AD (Leszek et al, 2016). Furthermore, previous studies have demonstrated that metabolic alterations such as insulin resistance (Arrieta-Cruz and Gutierrez-Juarez, 2016), hyperglycemia (Arrieta-Cruz and Gutierrez-Juarez, 2016), and dyslipidemia (Presecki et al, 2011) are associated with the pathogenesis and development of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Early onset of the disease, older age, low education level, and several poor health conditions affect the prevalence rate of the disease and the degree of cognitive impairment (de Souza-Talarico et al, 2016). Increased biomarkers of oxidative stress (Furman et al, 2016), inflammation and chronic neuroinflammation are reported to be associated with many neurodegenerative disorders of central nervous system (CNS) including AD (Leszek et al, 2016). Furthermore, previous studies have demonstrated that metabolic alterations such as insulin resistance (Arrieta-Cruz and Gutierrez-Juarez, 2016), hyperglycemia (Arrieta-Cruz and Gutierrez-Juarez, 2016), and dyslipidemia (Presecki et al, 2011) are associated with the pathogenesis and development of AD.…”
Section: Introductionmentioning
confidence: 99%
“…3D). Thus, incorporation of aggregated amylin in neurons is associated with elevated products of peroxidative membrane injury, similar to Aβ pathology [3032]. …”
Section: Resultsmentioning
confidence: 99%
“…Localized overabundance of free radicals leading to regional oxidative stress is one of the earliest abnormalities in neurodegenerative diseases, including AD, and in neurodevelopmental disorders such as AS (2, 516, 21, 8184). However, conventional imaging biomarkers cannot noninvasively measure region excess in free radical production in vivo.…”
Section: Discussionmentioning
confidence: 99%